1987
DOI: 10.1007/bf02116853
|View full text |Cite
|
Sign up to set email alerts
|

Microvascularization of the intracranial dura mater

Abstract: The authors have studied the microvascularization of the intracranial dura mater by microradiographic and histologic examination of 73 injected anatomic specimens. There exists a very abundant superficial arterial plexus which also serves to supply the inner table of the cranial vault. This plexus is continuous, even at the walls of the venous sinuses and the dural septa. The arteries are for the most part tortuous. The veins may be satellites of the arteries or, on the contrary, from a plexiform network passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 4 publications
3
40
0
Order By: Relevance
“…Roland et al 1987), which cannot be explained exclusively by the periosteal function of the cranial dura; practically the same density of vessels is found in the spinal dura ( Fig. 1), which does not serve any periosteal function.…”
Section: Selective Brain Cooling In Humans?mentioning
confidence: 88%
See 2 more Smart Citations
“…Roland et al 1987), which cannot be explained exclusively by the periosteal function of the cranial dura; practically the same density of vessels is found in the spinal dura ( Fig. 1), which does not serve any periosteal function.…”
Section: Selective Brain Cooling In Humans?mentioning
confidence: 88%
“…The dominant role is played by the external carotid arteries. All dural branches arising from these arteries show internal diameters between 400 and 800 ~tm and are interconnected by many intradural anastomoses that are found on the outer (periostal) surface of the dura (Kerber and Newton 1973;Roland et al 1987). These "primary anastomotic arteries" with more or less constant diameters of 100-300 ~tm, give rise to (1) numerous smaller arteries (40-80 ~tm i.d.)…”
Section: Vascular Arrangements In Human Meningesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no doubt that intracranial venous drainage plays a major role in the development of dAVE Many of these vascular malformations seem to develop after previous episodic thrombosis of the adjacent dural sinus [27,35]. It seems, that the process of recanalization of the sinus might be followed by the opening of arteriovenous shunts in the wall of the sinus due to the proximity of the arteries and veins into the dura [43]. In their experimental work Terada et al showed that increased intrasinusoidal pressure may play a role in the development of dAVF [48].…”
Section: Discussionmentioning
confidence: 99%
“…The dural membrane in rats is much thinner and therefore more transparent than in the human [10]- [11]. It might therefore be necessary to perforate the dura to make optical measurements from the human brain.…”
Section: Discussionmentioning
confidence: 99%